Impact of induced anxiety on neural responses to monetary incentives - Gorka, Adam X (Soc Cogn Affect Neurosci, 2018)
Previous research demonstrates that aversive stimuli can interrupt appetitive processing and that brain regions involved with the processing of potential rewards, such as the ventral striatum (VS), also respond to threatening information. Potential losses can likewise activate the VS and, thus, the full extent to which threat can impact neural responses during incentive processing remains unclear. Here, unpredictable threat of shock was used to induce anxiety while participants performed the monetary incentive delay (MID) task during functional magnetic resonance imaging (fMRI). During anticipation, anxiety impacted neural responses within the bilateral VS and distributed regions of the occipital cortex. Anxiety enhanced activity within the VS to both gain and loss trials. Furthermore, anxiety enhanced activity to both gain and loss trials within dorsal areas of BA19. However, anxiety only enhanced activity during gain, but not loss trials, within ventral areas of BA19. These results suggest that during anticipation, induced anxiety enhanced VS activity to incentives generally, which might reflect changes in the subjective salience of gains and losses. Collectively, these results suggest that the impact of induced anxiety on responses to monetary incentives depend on the neural region, type of incentive, and stage of processing.